A Study on Motivation, Occupational Identity and Coping Amongst Freshman Students of the National University of Public Service, Faculty of Law Enforcement - Sipos, Szandra (Magyar Rendészet, 2016)
Police career requires renouncement and considerable endurance, thus, it is essential for would-be police officers to be motivated and committed to police work and to have adaptive coping mechanisms. I carried out my research on the first day of the basic training amongst full time police students in 2011. My aim was to learn how motivated and committed these freshman students were, what stress coping mechanisms they had, and what extent of self-esteem they possessed. According to my research findings, police students arrive with great motivation, their self-esteem is high, and they possess problem-solving coping strategies.